Towards reliable uncertainties in IR interferometry: the bootstrap for correlated statistical and systematic errors. Issue 2 (16th January 2019) - Lachaume, Régis; Rabus, Markus; Jordán, Andrés; Brahm, Rafael; Boyajian, Tabetha; von Braun, Kaspar; Berger, Jean-Philippe
Abstract: We propose a method to overcome the usual limitation of current data processing techniques in optical and infrared long-baseline interferometry: most reduction pipelines assume uncorrelated statistical errors and ignore systematics. We use the bootstrap method to sample the multivariate probability density function of the interferometric observables. It allows us to determine the correlations between statistical error terms and their deviation from a Gaussian distribution. In addition, we introduce systematics as an additional, highly correlated error term whose magnitude is chosen to fit the data dispersion. We have applied the method to obtain accurate measurements of stellar diameters for underresolved stars, i.e. smaller than the angular resolution of the interferometer. We show that taking correlations and systematics has a significant impact on both the diameter estimate and its uncertainty. The robustness of our diameter determination comes at a price: we obtain 4 times larger uncertainties, of a few per cent for most stars in our sample.